Biological aspects of spotted seerfish Scomberomorus guttatus (Bloch & Schneider, 1801) (Scombridae) from north-eastern Arabian Sea - Anulekshmi, C.; Sarang, J. D.; Kamble, S. D.; Akhilesh, K. V.; Deshmukh, V. D.; Singh, V. V. (Indian Journal of Fisheries, 2018)
Spotted seerfish Scomberomorus guttatus (Bloch & Schneider, 1801) is one of the highly priced table fishes in India, which contributed 4.7% of all India scombrid fishery with 17,684 t landed in 2014. Its fishery is dominant in the Arabian Sea and northern Arabian Sea contributed 62% to India’s spotted seerfish fishery. Biological information on S. guttatus is scarce and the same was studied during the period 2010-2014 from Maharashtra coast, north-eastern Arabian Sea. A total of 930 specimens (185-550 mm FL) collected from commercial landings were used for the study. Length-weight relation of pooled sexes was estimated as log (W) = -3.1988+2.66074 log (L) (r2 = 0.93). Fishery was dominated by males with the sex ratio of 0.76:1. Relative fecundity ranged from 105-343 eggs g-1 of bodyweight. The length at first maturity (Lm) was estimated to be 410 mm TL for females. Mature and gravid females were dominant in May and August-November. Dietary studies (% IRI) showed dominance of Acetes spp.